Endemism of early cretaceous conifers in Western Gondwana - Archangelsky, Sergio; del Fueyo, Georgina Marisa
Early Cretaceous conifers occur in many parts of Western Gondwana.The families represented are the Araucariaceae, Cheirolepidiaceae, Podocarpaceae,and the taxodiaceous Cupressaceae. On the genus level, manytaxa have a global distribution; however, some of them are restricted tothe southern regions. In regard to species level, a great number of endemicsare located in southwestern Gondwana. This paleophytogeographicalarea extends from Patagonia to southern Africa in the east, to mid?SouthAmerica in the north, and probably as far as the Antarctic Peninsula in thesouth. These endemic taxa are characterized and discussed in this chapter.Endemism is especially strong among the podocarps and araucarians. Fil: Archangelsky, Sergio. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina Fil: del Fueyo, Georgina Marisa. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina